Evaluation of weekly COVID-19 vaccination and case data supports negative correlation between incidence and vaccination in German federal states and cities during 4th wave. Issue 22 (11th May 2022) - Springer, Steffen; Kaatz, Martin; Zieger, Michael
Highlights: The 7-day incidence is strongly negatively correlated with the vaccination rate during the course of 4th corona wave in Germany. The data support the trend that a high vaccination rate is correlated with a lower incidence. The importance of adequate vaccination for control of the coronavirus pandemic is underlined. Abstract: Global efforts have been made to end the COVID-19 pandemic. Among other things, various vaccines against SARS-CoV-2, partly based on novel principles, have been developed internationally within a short time. While initially the hardly available vaccines were distributed according to criteria according to defined priorities, in Germany, after the prioritization has been lifted, attempts are being made to provide as many people as possible with vaccinations. The study examines the relationship between vaccination and incidence in 16 German federal states and city states using data from the Robert Koch Institute (RKI). Clear trends became apparent, showing a negative correlation between the vaccination rate and the infection incidence. This indicates that during the 4th corona wave in Germany, the lower the incidence, the higher the vaccination rate.